Efeitos da Alamandina na função cardíaca pós isquêmica - Jônathas Fernandes Queiroz de Almeida (2015)
Myocardial infarction (MI) increases the susceptibility of heart failure and when occurs, it leads to cardiac remodeling. At the same time, the metabolic phenotype is also changed. Myocardial metabolic changes are directly linked with the humoral signaling. Then, we can say that renin angiotensin system (RAS) is considered critical in the regulation of ischemic heart disease and contributes to the pathophysiological consequences of MI. RAS is a widespread hormonal cascade composed of basically two counter regulatory axes. A classic axis, ACE / Ang II / AT1, and other axis, ACE2 / Ang- (1-7) / Mas. The role of Ang-(1-7) and its Mas receptor in infarction and reperfusion arrhythmia have been well studied, showing that it has significant cardio protective effects. Recently, Santos et al. (2013) described Alamandine as a new product of RAS. Formed by catalytic hydrolysis of the octapeptide Ala-Ang II (angiotensin A) by ACE2, Alamandine is an endogenous peptide of cardiac tissue very similar to Ang-(1-7), differing only in that one amino acid residue. Because of this proximity, most studied effects of Alamandine via MrgD receptor, are also similar to those of Ang-(1-7). Due to the recent description of Alamandine and its effects similar to Ang- (1-7), it is interesting to evaluating the effects of that heptapeptide in post-ischemic function in isolated rat hearts. Our data showed that Alamandina had significant cardioprotective effect by reducing the infarcted area, arrhythmias severity index and by preventing the decrease of left ventricular systolic pressure and maximum and minimum dP/dt. This review shows for the first time Alamandina showed significant cardioprotective effect in isolated rat hearts under ischemia reperfusion protocol.